Staging indigenous heritage : instrumentalisation, brokerage and representation in Malaysia - Cai, Yunci (London ; New York : Routledge/Taylor & Francis Group, 2020)
"Staging Indigenous Heritage examines the cultural politics of four Indigenous cultural villages in Malaysia. Cai demonstrates how they are often beset with the politics of brokerage and representation that reinforce a culture of dependency on the brokers, marginalising their intended beneficiaries. By critically examining the relationship between Indigenous tourism and development through the establishment of Indigenous cultural villages, the book addresses the complexities of adopting the 'culture for development' paradigm as a developmental strategy. Demonstrating that the opportunities for self-representation and self-determination can become entwined with the politics of brokerage and the contradictory dualism of culture, the book shows how this can both facilitate and compromise their intended outcomes. Challenging the simplistic conceptualisation of Indigenous communities as harmonious and unified wholes, Cai shows how Indigenous cultures are actively forged, struggled over and negotiated in contemporary Malaysia Confronting the largely positive rhetoric in current discourses on the benefits of community-based cultural projects, Staging Indigenous Heritage should be essential reading for academics and students in the fields of museum studies, cultural heritage studies, Indigenous studies, development studies, tourism, anthropology and geography. The book should also interest museum and heritage professionals around the world"--
Chapter 1: IntroductionChapter 2: Historicising Indigeneity in MalaysiaChapter 3: Capacity-building as a modern civilising missionChapter 4: Indigeneity as an intractable double-bindChapter 5: Appropriation, reinvention, and contestation of Indigenous heritageChapter 6: The big man as arbitrator of heritageChapter 7: Conclusion
OCLC-licensed vendor bibliographic record.
Keywords: Orang Asal (Malaysian people); Ethnology -- Malaysia; Villages -- Malaysia; Heritage tourism -- Malaysia; Cultural villages